Impersonations : the artifice of Brahmin masculinity in South Indian dance - Kamath, Harshita Mruthinti, 1982- (University of California Press, 2019)
"Impersonations: The Artifice of Brahmin Masculinity in South Indian Dance centers on an insular community of Smarta Brahmin men from the Kuchipudi village in Telugu-speaking South India who are required to don stri-vesam (woman's guise) and impersonate female characters from Hindu religious narratives. Impersonation is not simply a gender performance circumscribed to the Kuchipudi stage, but a practice of power that enables the construction of hegemonic brahmin masculinity in everyday village life. However, the power of the brahmin male body in stri-vesam is highly contingent, particularly on account of the expansion of Kuchipudi in the latter half of the twentieth century from a localized village performance to a transnational Indian dance form. This book analyzes the practice of impersonation across a series of boundaries--village to urban, brahmin to non-brahmin, hegemonic to non-normative--to explore the artifice of brahmin masculinity in contemporary South Indian dance"--Provided by publisher